EKG Electrode as a Tactile Locator of Stoma after Decannulation: A Pilot Study. Issue 1 (February 2017) - Garcia-Rodriguez, Laura; Miah, Tayaba; Lindholm, Jamie; Chang, Steven; Ghanem, Tamer
Objective: We aimed to evaluate the use of an electrocardiogram (EKG) electrode over decannulation dressings covering the stoma to improve speech intelligibility and volume and reduce air escape by facilitating identification of the "sweet spot" of the dressing. No objective data exist for patient outcomes with use of the EKG electrode dressing. Methods: This prospective study included head and neck oncology patients at a tertiary hospital who received a tracheostomy. A standard tracheostomy decannulation dressing was placed followed by an EKG electrode. A speech pathologist evaluated speech volume via sound-level meter and captured speech intelligibility for random sentence-level speech. A blinded reviewer scored speech samples for intelligibility. Patients completed a 4-question satisfaction survey. Results: Four patients completed the study. Based on the survey, the patients favored the button, with the lowest scores being 8.5 out of 10. Speech understanding was 48.5% without the button and 83% with the button. Normal speech volume was 73.75 dB without the button and 77.75 dB with the button. Loud speech volume was 80.75 dB without the button and 87 dB with the button. Discussion: This pilot study shows objective benefits of the EKG button as well as improved patient satisfaction. Inexpensive and low maintenance, the EKG electrode provides better occlusion of stoma dressing with easier localization. Implications for Practice: Dissemination of our results will aim to improve quality and patient outcomes following decannulation.